Public transport planning with smart card data - Kurauchi, Fumitaka; Schmocker, Jan-Dirk (CRC Press/Taylor & Francis, 2017)
The book discusses theory as well as applications from cities around the world and will be of interest to researchers and practitioners alike who are interested in the state-of-the-art as well as future perspectives that smart card data will bring.